Hope and positive affect mediating the authentic leadership and creativity relationship - Rego, A. (2015)
The study analyzes how authentic leadership (AL) predicts employees' creativity both directly and through the mediating role of employees' positive affect and hope. Two hundred and three employees working in Portuguese retail organizations participate in the research. Employees report their hope and positive affective states, as well as the AL of their supervisors. Supervisors report the employees' creativity. The main findings are: (a) AL predicts employees' creativity, both directly and through the mediating role of employees' hope; (b) AL also predicts employees' positive affect, which in turn predicts employees' hope and, thus, creativity. The study enriches the understanding of the processes through which AL improves employees' creativity, and provides valuable insights for both scholars and practitioners. By promoting AL, and employees' hope and positive affect, organizations may increase employees' creative performance, creativity being an important path to organizational performance